â€œOriaku Vs Okpatakuâ€: The Changing Roles of Femininity within The Patriarchal Igbo Tradition in Nigeria - Ifeoma Ojiakor; Adeline Nkwam-Uwaoma; Collins C Awaeze; Emeka Williams Etumnu (UIN Sunan Gunung Dajti Bandung, 2023)
Over time, the ease of access has been to the advantage of men and the disadvantage of women, especially in a traditional society like Nigeria. However, despite the marginalization, it appears that women are beginning to challenge norms, traditions, cultures, and stereotypes by breaking free from the shackles of patriarchy. Hence, this study examines the current perception of femininity concerning employment and income. Specifically, it aimed at understanding how the clamor for gender equality and equity has changed one of the characteristics of femininity from â€œOriakuâ€ to â€œOkpatakuâ€ in a typical patriarchal society like Anambra State, Nigeria. Using the Constructionist Theory of representation as a framework, the study adopts in-depth interviews as a qualitative approach. Findings reveal that both men and women are more comfortable with being Okpataku than Oriaku, owing to the recent harsh economic reality in the country. Recommendations were made based on the findings.